The Identification of Intrinsic Chloramphenicol and Tetracycline Resistance Genes in Members of the Bacillus cereus Group (sensu lato) - Glenwright, Helen; Pohl, Susanne; Navarro, Ferran; Miro, Elisenda; Jiménez, Guillermo; Blanch, Anicet R.; Harwood, Colin R. (Frontiers in Microbiology, 2017)
Bacillus toyonensis strain BCT-7112T (NCIMB 14858T) has been widely used as an additive in animal nutrition for more than 30 years without reports of adverse toxigenic effects. However, this strain is resistant to chloramphenicol and tetracycline and it is generally considered inadvisable to introduce into the food chain resistance determinants capable of being transferred to other bacterial strains, thereby adding to the pool of such determinants in the gastro-enteric systems of livestock species. We therefore characterized the resistance phenotypes of this strain and its close relatives to determine whether they were of recent origin, and therefore likely to be transmissible. To this end we identified the genes responsible for chloramphenicol (catQ) and tetracycline (tetM) resistance and confirmed the presence of homologues in other members of the B. toyonensis taxonomic unit. Unexpectedly, closely related strains encoding these genes did not exhibit chloramphenicol and tetracycline resistance phenotypes. To understand the differences in the behaviors, we cloned and expressed the genes, together with their upstream regulatory regions, into Bacillus subtilis. The data showed that the genes encoded functional proteins, but were expressed inefficiently from their native promoters. Bacillus toyonensis is a taxonomic unit member of the Bacillus cereus group (sensu lato). We therefore extended the analysis to determine the extent to which homologous chloramphenicol and tetracycline resistance genes were present in other species within this group. This analysis revealed that homologous genes were present in nearly all representative species within the Bacillus cereus group (sensu lato). The absence of known transposition elements and the observations that they are found at the same genomic locations, indicates that these chloramphenicol and tetracycline resistance genes are of ancient origin and intrinsic to this taxonomic group, rather than recent acquisitions. In this context we discuss definitions of what are and are not intrinsic genes, an issue that is of fundamental importance to both Regulatory Authorities, and the animal feed and related industries.